Ibrahim-i Gulshani and the Khalwati-Gulshani Order : power brokers in Ottoman Egypt - Emre, Side. (Studies on Sufism, 2017)
In Power Brokers in Ottoman Egypt , Side Emre documents the biography of Ibrahim-i Gulshani and the history of the Khalwati-Gulshani order of dervishes (c. 1440-1600). Set mainly in Mamluk-Egypt, and in the century following the region's conquest by the Ottomans, this book analyzes sociopolitical dialogues at the geographic peripheries of an empire through the actions of and official responses to the Gulshaniyya network. Emre argues that the members of this Sufi order exerted social and political leverage and contributed significantly to the political culture of the empire and Egypt. The Gulshanis are uncovered as unexpected figures among the roster of influential players, in contrast with empire-centered historiographies that depict Ottoman ruling and learned elites as the primary shapers and narrators of the fates of conquered provinces and peoples. The Gulshanis' political and cultural legacy is situated within an analysis of perceptions of Sufism in the early modern Ottoman world.